Influence of calcium ions on physical chemical characteristics of semiconductor quantum dots encapsulated by amphiphilic polymer and their efficiency of cellular uptake - Radchanka, Aliaksandra V.; Terpinskaya, Tatiana I.; Yanchanka, Tatsiana L.; Balashevich, Tatjana V.; Artemyev, Mikhail V. (Journal of the Belarusian State University. Chemistry, 2020)
Here, we studied the effect of calcium ions on the physicochemical properties and cellular uptake of CdSe/ZnS quantum dots encapsulated with poly(maleic anhydride-alt-1-tetradecene), modified to a varying extent by quaternary ammonium groups. It was shown that quantum dots carrying negatively charged carboxyl groups in the polymer shell change their physicochemical and optical characteristics in the presence of Ca2+ and Ba2+ ions. As the negatively charged carboxyl groups in the shell are completely replaced by positively charged quaternary ammonium groups, these effects gradually decrease. A change in the physicochemical properties of nanoparticles leads to a change in their cellular uptake in the presence of calcium ions. Nanoparticles carrying only negatively charged groups in the shell in the presence of Ca2+ agglomerate and form conglomerates of nanoparticles and cells. The positively charged quaternary ammonium groups in the polymer shell of the nanoparticles increase their aggregative stability in the presence of Ca2+ and contribute to their uptake by cells. The mechanisms of uptake depend on nanoparticle’s charge. Nanoparticles with a positive ζ potential are absorbed by calcium-dependent mechanisms, which are suppressed by inhibition of the calcium-dependent enzyme dynamin or in the presence of calcium chelator EGTA. The uptake of nanoparticles with a negative ζ potential, in contrast, is enhanced by the chelation of calcium ions. This indicates the different role of cellular calcium-dependent mechanisms in the uptake of positively and negatively charged nanoparticles.
Keywords: quantum dots; amphiphilic polymer; zeta-potential; calcium ions; cellular uptake